A crook is a crook ... but is he still a crook abroad? On the effect of immigration on destination-country corruption - Eugen Dimant; Tim Krieger; Margarete Redlin (Albert-Ludwigs-Universität Freiburg, Wilfried-Guth-Stiftungsprofessur für Ordnungs- und Wettbewerbspolitik, 2013)
This paper analyzes the impact of migration on destination-country corruption levels. Capitalizing on a comprehensive dataset consisting of annual immigration stocks of OECD countries from 207 countries of origin for the period 1984 - 2008, we explore different channels through which corruption might migrate. Independent of the econometric methodology applied, we consistently find that while general migration has an insignificant effect on the destination country's corruption level, immigration from corruption-ridden origin countries boosts corruption in the destination country. Our findings provide a more profound understanding of the economic implications associated with migration flows.
Keywords: D73; F22; O15; 330; corruption; migration; impact of migration